Acute retroviral syndrome presenting as encephalitis and cerebellar ataxia: case report and literature review - Chang Sedano, Lyan (2024)
Acute retroviral syndrome (SRA) is one of the possible clinical scenarios in the early stages of HIV infection, with varying presentations, characterized by high viral copies and nonspecific symptoms. We describe the case of a 21-year-old man who presented with acute onset encephalopathy and cerebellar ataxia which led to the diagnosis of HIV, in whom the diagnosis of SRA was established.